NIMG-15. EVALUATING FLUCTUATING ENHANCEMENT IN OLIGODENDROGLIOMAS ON MAGNETIC RESONANCE IMAGING. (9th November 2020) - Barbaro, Marissa; Pan, Peter; Pisapia, David; Schwartz, Theodore; Ramakrishna, Rohan; Knisely, Jonathan; Fine, Howard; Chiang, Gloria; Magge, Rajiv
Abstract: OBJECTIVE: To identify and characterize patterns of fluctuating contrast enhancement on magnetic resonance imaging (MRI) in patients with oligodendrogliomas. INTRODUCTION: Gliomas, particularly oligodendrogliomas, can exhibit fluctuating enhancement (FE) on MRI that can make it difficult to differentiate between treatment effect and active tumor. METHODS: We are conducting a single-center retrospective review of clinical and radiographic data for patients with oligodendrogliomas treated at Weill Cornell Medicine (WCM) from 2/2000-5/2018. We have identified patients with FE on MRI and tracked lesions > 5mm in at least one dimension to the resolution of the lesion or last available MRI. We have recorded time from initial diagnosis to development of FE, time from radiation to development of FE, and time from development to resolution of FE as well as molecular characteristics of each tumor. RESULTS: A total of 122 patients with oligodendrogliomas were identified. Thus far, fluctuating enhancement has been identified in 11 patients (5 men, 6 women) with 38 total fluctuating lesions. Isocitrate dehydrogenase-1 (IDH-1) mutation was present in 5 tumors, and 1p/19q co-deletion was present in 6. Mean time from initial diagnosis to development of FE was 44.6 months. In patients who developed FE after radiation, mean time from radiation to development of FE was 35.0 months. Twenty-seven lesions resolved, and mean time from onset to resolution of FE was 5.6 months, while mean time from start of radiation to resolution of FE was 41.0 months. Additionally, we will perform perfusion analysis on lesions > 5mm and identify patients who underwent surgical biopsy of FE with pathologic diagnosis. CONCLUSIONS: FE has been identified in 11 patients thus far. We are expanding our analysis to identify a larger cohort of patients with FE. Characterizing patterns of FE may aid clinicians in differentiating FE due to treatment effect from active tumor.